Demyelinating Charcot–Marie–Tooth neuropathy associated with FBLN5 mutations. (5th September 2020) - Safka Brozkova, D.; Stojkovic, T.; Haberlová, J.; Mazanec, R.; Windhager, R.; Fernandes Rosenegger, P.; Hacker, S.; Züchner, S.; Kochański, A.; Leonard‐Louis, S.; Francou, B.; Latour, P.; et al.
Abstract : Background and purpose: Charcot–Marie–Tooth disease type 1 (CMT1) is a group of autosomal dominantly inherited demyelinating sensorimotor neuropathies. Symptoms usually start in the first to second decade and include distal muscle weakness and wasting, sensory disturbances and foot deformities. The most frequent cause is a duplication of PMP22 whilst point mutations in PMP22 and other genes are rare causes. Recently, FBLN5 mutations have been reported in CMT1 families. Methods: Individuals with FBLN5 ‐associated CMT1 were compiled from clinical and research genetic testing laboratories. Clinical data were extracted from medical records or obtained during patients' visits at our centres or primary care sites. Results: Nineteen CMT1 families containing 38 carriers of three different FBLN5 missense variants were identified and a mutational hotspot at c.1117C>T (p.Arg373Cys) was confirmed. Compared to patients with the common PMP22 duplication, individuals with FBLN5 variants had a later age of diagnosis (third to fifth decade) and less severely reduced motor median nerve conduction velocities (around 31 m/s). The most frequent clinical presentations were prominent sensory disturbances and painful sensations, often as initial symptom and pronounced in the upper limbs, contrasting with rather mild to moderate motor deficits. Conclusions: Our study confirms the relevance of FBLN5 mutations in CMT1. It is proposed to include FBLN5 in the genetic work‐up of individuals suspected with CMT1, particularly when diagnosis is established beyond the first and second decade and comparably moderate motor deficits contrast with early and marked sensory involvement. FBLN5 ‐associated CMT1 has a recognizable clinical phenotype and should be referred to as CMT1H according to the current classification scheme.